Пошуково-дослідницький проект «Ставлення українців до історичного минулого» в рамках якісної стратегії соціологічного дослідження - Ліщук-Торчинська, Тетяна Петрівна; Lishchuk-Torchynska, Tetiana (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті на основі конкретного досвіду обґрунтовано перспективність використання проектної технології під час вивчення студентами-соціологами курсу «Якісні методи у соціологічних дослідженнях». Розглянуто теоретичні питання, методичні й організаційні аспекти проведених у рамках проекту досліджень. На основі біографічного та усно-історичного типів якісної стратегії дослідження за допомогою методів глибинного інтерв’ю й фокус-груп апробовано комплексний підхід до розгляду ставлення українців до історичного минулого. У межах цього проекту розкрито значення для фахової підготовки соціологів у вищій школі дидактичної та змістової складових частин польової роботи студентів. Суть першої з них полягає в поглибленні розуміння студентами дослідницького процесу за допомогою застосування теорії, методів і процедури дослідження в практиці польової роботи, відпрацюванні способів аналізу даних; у самоаналізі та самооцінці рівня фахової підготовки з курсу. Суть іншої – у залученні студентів до вивчення актуальної для українського суспільства теми розмислів над історичним минулим репрезентантів різних статусних груп. Під час участі в проекті студенти в рамках якісної стратегії соціологічного дослідження здобули досвід пошуково-дослідницької роботи включно з досвідом генерування й критики ідей, командної та індивідуальної роботи, досвідом взаємодії в «полі» з іншими. The article is based on concrete experience that substantiates the prospects of using the projective technology during the study «Qualitative Methods in Sociological Research» course by students of sociology department. The project was implemented during 2015/2016 and 2016/2017 academic years by students of sociology department of «Master» and «Specialist» degree of the Lesya Ukrainka Eastern European National University; the project was headed by the author of the article. The geography of the study has covered Volyn, Lviv, Rivne, Ternopil and Charkiv regions of Ukraine. The sample of the study consisted of representatives of various status groups: ordinary citizens aged 60 and older (in the narrative interview format), experts – representatives of the humanitarian intelligentsia aged from 35 to 60 years (in a semi-structured interview format) and of young intellectuals that are students (in focus group studies). The theoretical questions, methodological and organizational aspects of empirical researches that were carried out within the framework of the project are considered. On the basic of biographical type and type of oral history of qualitative research strategy within the help of methods of in-depth interviews and focus-groups an integrated approach to the study of the attitude of Ukrainians towards the historical past has been tested. Within the framework of this project, the significance for the professional preparation of sociologists in the high school of the didactic and content components of field work of students was revealed. The essence of the first of these components is to deep students’ understanding of the research process by applying the theory, methods of data analysis applying self-assessment of the level of the course professional training. The essence of another is in attracting students to the study of topics relevant to the Ukrainian society over the historical past of the representatives of various status groups. While participating in the project, with the framework of a qualitative sociological research strategy, students gained experience of search and research work, including the experience of generation and critics of ideas, teamwork and individual work, interaction in the field with the Others.
Search and Research Project «Attitude of Ukrainians to the Historical Past» in the framework of Qualitative Strategy of Sociological Research
Keywords: метод проектів; біографічне дослідження; усна історія; глибинне інтерв’ю; фокус-група; project method; biographical research; narrative interviews; oral history; semi-structured interviews; focus group